(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research investigates the potential antisickling effects of Carica papaya unripe fruit extracts on HbSS red blood cells from non-crisis state sickle cell patients. Utilizing the soxhlet extraction method with various solvents, the dried unripe fruit of C.